Assessing the Extent to which Customer Feedback Contributes to Value Co-Creation: A Focus on the Tourism Industry - Mgoduka, Siyasanga; Kaseeram, Irrshad; Heeralal, Shalen (Journal of Sustainable Development Law and Policy, 2025)
Over the past few decades, the process of creating economic value has changed from single companies contributing individually to co-creating value and integrating customer knowledge into product development. Firms are creating value through the use of engagement experiences between customers and firms. The new locus of value co-creation is interactions between firm stakeholders and customers; hence, organisations need to be designed to revolve around these interactions to identify opportunities for customercompany co-creation. Nonetheless, there are still a lot of unanswered questions regarding value co-creation, its antecedents, and its effects. Literature on the effects of customer feedback on value co-creation is sparse, the existing body of knowledge lacks information regarding the role played by customer feedback to enhance the co-creation of value between firms and their consumers. In context with this, the study aims to assess the extent to which customer feedback contributes to value co-creation by focusing on the tourism industry. In addressing the aforementioned gap, this study employed the Service – dominant (S–D) Logic Theory. Moreover, purposive sampling was used in this study to gather qualitative data from 20 guests who made visits to the 23 targeted game and nature reserves in Mpumalanga. The findings revealed that customer feedback such as preferences and opinions about products and services enhances value co-creation. Moreover, the findings revealed that the use of social media platforms to allow consumers to make suggestions and comments about a service provision enhances value cocreation. This study therefore concludes that firms must encourage customer feedback to enhance value co-creation.